Molecular characterisation of radish cultivars - Cruz, Sara; Nery, Marcela; Von Pinho, Édila; Laia, Marcelo (Revista Ciência Agronômica, 2014)
The radish has been gaining importance in the Brazilian market due to its use as a green manure and cover crop, and also due to its potential for the production of biodiesel, however there are only two registered cultivars, which are morphologically very similar. Determination of genetic purity is a prerequisite in marketing seeds as it ensures uniformity of the crop and is important in breeding programs. The aim of this work therefore was to evaluate the similarity and genotype patterns which permit differentiation of the commercial radish cultivars IPR 116 and CATI AL-1000. In order to do this, isoenzyme electrophoretic patterns were analysed in dry seeds, soaked seeds, seedling leaves and young leaves; the isoenzymes used being: superoxide dismutase, catalase, esterase, glutamate-oxalocetate, malate dehydrogenase and isocitrate lyase. Thirty-seven RAPD primers and 10 ISSR primers in leaves of the CATI AL-1000 and IPR-116 cultivars were analysed. Among the isoenzymes under study, the most polymorphic were glutamate oxalocetate, malate dehydrogenase, esterase and superoxide dismutase, with the superoxide dismutase system giving the best characterisation for all stages of development. The catalase isoenzyme system did not make it possible to differentiate between cultivars at any stage of development, and isocitrate lyase was not revealed by the protocol used. In analysis of the markers, 27 RAPD primers and eight ISSR primers showed polymorphism. The results indicate that it is possible to determine reliable descriptors based on isoenzymes at different stages of development of the radish and with the use of RAPD and ISSR primers.